Web Application to Build Information System of National Seminar Alerts in Indonesia - Erlin Erlin; Khusaeri Andesa; Agustin Agustin (Institute of Advanced Engineering and Science, 2018)
The output of research in the form of a proceeding published through a national seminar or an international conference has become a routine activity performed by lecturers as a researcher. The escalating atmosphere of disseminating the results of a study is directly proportional to the increasing number of universities, associations, or non-educational institutions organizing either a national seminar or an international conference. Each seminar organizer posts their seminar relevant information through official sites released by each organizer. However, to date, there has never been storage that can compile all the information pertinent to all national seminars held in Indonesia. This situation has resulted in the search done by search engines such as Google, Yahoo Search, Bing and others have not been efficient nor effective. Design of a web-based national seminar alert system is built to address this issue. This information system can display all the seminars held in Indonesia in the current year in storage and can be broken down based on the choices of topic, location, and date. Other additional facilities are that the application can send email messages to the application users as an early warning on the upcoming national seminar. Researchers can track each existing national seminar and always up-to-date on the most current national seminar.